Are psychogenic non-epileptic seizures just another symptom of conversion disorder?. Issue 5 (24th February 2017) - Kanaan, Richard A A; Duncan, Roderick; Goldstein, Laura H; Jankovic, Joseph; Cavanna, Andrea E
Abstract : Background: Psychogenic non-epileptic seizures (PNES) are classified with other functional neurological symptoms as 'Conversion Disorder', but there are reasons to wonder whether this symptomatology constitutes a distinct entity. Methods: We reviewed the literature comparing PNES with other functional neurological symptoms. Results: We find eight studies that directly examined this question. Though all but one found significant differences—notably in presenting age, trauma history, and dissociation—they were divided on whether these differences represented an important distinction. Conclusion: We argue that the aetiological and mechanistic distinctions they support, particularly when bolstered by additional data, give reason to sustain a separation between these conditions.